اختلاف مصطلاحات الوقف بين العلماء وموازنته على رأي الجمهور - Ahmad, A. M. (Universiti Sains Islam Malaysia, 2024)
The science of endowment and initiation has received great attention from Muslim scholars - past and present - and they have written many books on the different approaches to it. Some of them singled out the authorship and took care of the provisions of the waqf and begin with verses of the Quran head and middle separately. And some of them made it a chapter of their books, and he explained the rules of endowment and start and its types, with examples for each of those rules and types. Those who reflect on these books, find that they were not agreed on the same terms in the division of endowment and commencement, but for each owner of the terms reliable and reliable. The terminology may be the same and the purposes for it are different, while others may reflect this. These various different terms may lead to confusion in the understanding of the ruling on the endowment for the verse, especially for the initiators of these books, so they mistook the understanding of the endowment for the verses and their ruling. This study attempted to raise this terminological complexity between these books, by describing what is meant by both the terms endowment and starting used in books and starting, and then compare and measure them on the scale of the divisions of the majority of scholars of this art. In order to achieve these goals, the study chose some basic sources in this field, namely: Explanation of the endowment and commencement of Al-Anbari, cutting and plotting of copper, and Manar Al-Huda in explaining the endowment and beginning of al-Ashmuni, as a model for this study. One of the important results of this study is that some of these terms are agreed in both terms and purposes together, and as I am for others in terms of terms, but its purposes are different. The study also discovered that some of these terms are intertwined with each other.